(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: Branch Retinal Vein Occlusion (BRVO) is a common retinal vascular disorder which involves one of the branch retinal veins. The aim of the study is to analyse epidemiology, risk factors, clinical characteristics in the distribution of different types of BRVO and final visual outcome after treatment and six months follow up. Materials and Methods: This is a prospective study including 222 patients of BRVO was done from October-2018 to September-2020. Clinical evalution included, detailed history with systemic risk factors, visual acuity testing, Slit-lamp biomicroscopy, Intra occular pressure, detailed fundus evaluation, fundus fluorescein angiography, Optical Coherence Tomography and Gonioscopy. Laboratory test included complete blood count, Erythrocyte sedimention rate, fasting blood sugar, serum lipid profile. Treatment given, observation and follow up, intravitreal (lV) ranibizumab, IV triamcinolone and laser photo coagulation. Results: Out of 222 BRVO patients, 207 (94.1%) were major BRVO (129(58.1%) were suprotemporal BRVO, 66(29.8%) were inferotemporal BRVO) and 15 (5.9%) were macular BRVO. Maximum number of patients 108 (48.6%) in the age group of 61-70 years. Male patients 126 (56.7%) more than females 96 (43.3%). Right eye 117 cases (52.7%) were involved slight more than the left eye 102 cases (45.9%). Blurring of vision 162 (72.9%) is the commonest symptom. Hypertensive patients 113 (50.9%) affected more followed by Diabetic 36 (16.2%) and cardiovascular disease 33 (14.9%). Mean Systolic blood pressure (SBP), Diastolic blood pressure (DBP), ESR & Fasting blood sugar (FBS) are higher in Macular BRVO, cholesterol level is higher in Major BRVO. Retinal haemorrhage was present in all cases. Macular edema was present in 87.4% of patients in whom OCT was done. At the end of six months after treatment in majority of patients i:e 85.1% had BCVA between 6/6-6/18. There was dramatical improvement of vision after receiving intravitreal Ranibizumab (P value 0.041). Conclusion: There is strong association of conventional risk factors with BRVO. Visual prognosis depends on initial status with careful monitoring for macular ischaemia, macular edema, development of neovascularization and subsequent neovascular glaucoma followed by appropriate therapy like IV Ranibizumab, IV Triamcinolone and laser photocoagulation etc wherever required. There is dramatical improvement of vision after receiving intravitreal Ranibizumab (P value 0.041).